3D FDTD Method for Modeling of Seismo-Electromagnetics Disturbance on Crustal Earth - Shabrina, Nabila Husna; Hobara, Yasuhide; Munir, Achmad (UI Scholars Hub, 2019)
The paper deals with the modelling of seismo-electromagnetics disturbance on the crustal earth by use of threedimensional (3D) finite-difference time-domain (FDTD) method. The model is built up by discretizing the frontier geographical region between Java Island and Sumatra Island in a cylindrical coordinate system-based 3D object. The proposed method is applied to compute and analyze electromagnetics (EM) fields of the observed very low frequency (VLF) wave used for the investigation. Boundary condition of uniaxial perfectly matched layer (UPML) are applied surrounding the area of computation for truncating the object of simulation. The investigation are focused on the propagation time of observed VLF wave and its amplitude variation between the observation point and disturbance pulse. The result shows that the propagation time is significantly affected by the distance of observation point and the permittivity of propagation medium. Meanwhile, the addition pulse associated with the earthquake influences the amplitude of observed VLF wave instead of its frequency.